Data Privacy in the Age of Cloud: Ethical Considerations and Impacts on Society - Rohini Isarapu; Sharathchandra Gowda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The widespread adoption of cloud computing has fundamentally transformed how organizations manage and protect data, introducing complex privacy challenges alongside unprecedented opportunities. This comprehensive article explores the ethical considerations and societal impacts of data privacy in cloud environments, examining how organizations navigate consent mechanisms, data ownership, and regulatory compliance. The article investigates the evolution of data collection practices, the implementation of privacy frameworks, and the critical role of corporate responsibility in maintaining stakeholder trust. By examining industry research and real-world implementations, this article demonstrates the intricate relationship between technical innovation, ethical governance, and societal expectations in cloud-based data privacy, highlighting the importance of balanced approaches that protect individual privacy while enabling organizational growth and innovation.